OPTIMALISASI PRODUKSI PAKAN KOI (Cyprinus carpio) SECARA MANDIRI BERBAHAN BAKU LOKAL DI CV INDOKOI MALANG - Ganjar Adhywirawan Sutarjo; Riza Rahman Hakim; Dony Prasetyo; David Hermawan; Nur Subeki; Warkoyo Warkoyo; Yohana Agustina; Anis Zubaidah (Jurnal Abdi Insani, 2023)
Independent koi fish feed production activities are an effort made to fullfill feed availability for cultivation. Beside that, it can also be used as a business opportunity to market koi fish feed products for partners. However, this effort has challenges in managing it, one of which is the lack of knowledge and skills of program partners in the stages of the independent koi feed production process. The aim of implementing this activity is to increase the knowledge and skills of human resources (workforce) of program partners in making independent koi feed, especially in operating limited-scale feed production equipment at CV. Indokoi Malang. The method used in carrying out this activity is through a socialization approach and training on techniques for making independent koi fish feed based on local raw materials. This activity is carried out by providing training on the operation of limited-scale independent fish feed production equipment. The result of this activity was the implementation of training activities which were attended by 30 participants consisting of the implementing team, partners and students. Apart from that, koi fish food products were also obtained according to the quality target and capacity of the independent koi food production machine. The results of the activity evaluation showed an increase in partners' understanding (by 40%) regarding skills in making fish food as well as an increase in partners' abilities in operating limited-scale feed production equipment machines. The conclusion of this activity is that this training can improve the skills and knowledge of partners in producing koi fish feed independently.